EFEKTIVITAS MODEL PEMBELAJARAN SCIENCE TECHNOLOGY SOCIETY (STS) DISERTAI DENGAN MIND MAP (MM) UNTUK MEMBERDAYAKAN KETERAMPILAN PROSES SAINS SISWA - Ivayuni Listiani (Universitas PGRI Madiun, 2015)
The purpose of this study was to determine the effectiveness of a Science Technology Society model accompanied with Mind Map to empower the ability to science procces skills. This study was a quasi-experimental study. The study used a one-group pretest-posttest design. The population of the study was all students of grade X of Public Senior High School 7 Surakarta in the academic year of 2013/2014. Sample was taken using cluster random sampling technique with a sample of 27 students. The instrument used was questionnaire, observation sheets, interviews, and tests. The ability to KPS data was tested with the Paired sample t-test and calculated by Ngain. The results showed the effectiveness of STS models accompanied with MM, in which it had been successful in increasing the ability to KPS with a value of Ngain of 0.54 and the result was significance at p=0.000, making the ability belong to “medium” category. Based on the results of research and hypothesis testing, it can be concluded that STS model accompanied with MM was effective in empowering the ability to KPS of the tenth graders of Senior High School 7 Surakarta in the academic year of 2013/2014.